Cashless payment and corruption in the context of country legal institutions: Evidence from Vietnam - Le, Thi Thuy Hang; Nguyen, Tuan Duy; La, Quoc Trung; Nguyen, Huynh Bao Han; Vu, Van Nhi; Pham, Thi Xuan Trang; Ngo, Nhut Duy (Journal of Finance - Marketing Research, 2025)
Corruption remains a critical issue in modern society, with far-reaching consequences for economic growth, governance, and social stability. While extensive research has explored its causes and influencing factors across different countries, findings have often been inconsistent due to variations in institutional frameworks and governance structures. This study examines the complex relationship between corruption, non-cash payment systems, the rule of law, and management quality using data from Vietnam between 2002 and 2022. By applying Wavelet and Breitung-Candelon tests, the analysis uncovers a bidirectional relationship between management quality and both corruption and non-cash payment adoption, suggesting that stronger governance can play a key role in both reducing corruption and fostering digital transactions. However, the findings indicate that the rule of law does not exhibit a clear or direct impact on the connection between non-cash transactions and corruption, implying that legal frameworks alone may not be sufficient to drive financial and governance reforms. Instead, improving institutional efficiency and management practices appears to be a more effective approach in enhancing financial transparency and economic accountability. These insights highlight the necessity of targeted policy interventions that prioritize governance improvements and digital financial innovations to create a more transparent and resilient economic system.